Pelatihan Uji Nilai California Bearing Ratio bagi Mahasiswa Teknik Sipil - Wardana Galih Pamungkas; Muhammad Latif; Sulistyowati Sulistyowati (Faculty of Engineering, Universitas Semarang, 2025)
CBR (California Bearing Ratio) is a soil-bearing capacity test developed by the California State Highway Department. The principle of this test is penetration testing, which inserting an object into the sample. This way, the strength of the base soil or other materials used to make road pavements can be assessed. The main problem in this report is the lack of understanding and skills of civil engineering students in conducting CBR tests, and in assessing the bearing capacity of the base soil as a foundation layer of road pavements. Students are often constrained in understanding the basic principles of CBR tests, the use of laboratory equipment, and the interpretation of test results. This activity aims to improve student understanding through a combination of theoretical learning methods, discussions, and direct practice in the laboratory using standard procedures SNI 1738-2011 and SNI 1744-2012. The implementation of the test involves soil sample preparation, CBR test penetration testing, and analysis of results through a graph of the relationship between load and penetration depth. The results show that the increase in student understanding, as evidenced by the difference in pre-test and post-test scores indicated an increase in test implementation and analysis of the results. Students who initially did not understand the procedure and importance of CBR testing are now able to use it in the context of road pavement planning. In conclusion, this training has succeeded in improving students' competence in understanding and applying CBR testing, which will support them in civil engineering practices, especially in the design and analysis of road structure resistance based on soil-bearing capacity.